The lipase-catalyzed synthesis of fatty acid fructose esters in organic media and in supercritical carbon dioxide - Šabeder, Saša; Leitgeb, Maja; Knez, Željko (Chemical Industry and Chemical Engineering Quarterly, 2012)
Sugar fatty acid esters are biodegradable surface active compounds in foodstuffs and cosmetics or pharmaceuticals. They have potential in replacing pollutant chemically synthesized surfactants. The enzymatic synthesis of fructose palmitate catalyzed by Candida antarctica B lipase was performed in different organic media in a batch react at atmospheric pressure. The influence of the organic solvent and temperature on the esterification was studied. Since supercritical carbon dioxide (SC CO2) has several advantages over organic solvents, such as high reaction rate, high mass transfer, non-toxicity, non flammability and low price, it was also chosen as a reaction medium for fructose palmitate production. The influence of temperature on immobilized lipase activity was studied at 10 MPa and the results were compared to the results obtained from reactions performed at atmospheric pressure under the same reaction conditions. The highest conversion (67%) was obtained after 24 hours of reaction in SC C02 at 80°C. A change of the particle size distribution and morphology of the untreated lipase and lipase treated with 2-methyl 2-butanol and SC C02 was observed. This article was presented at 1st SEECChE, held in Belgrade, September 25-28, 2005 Estri šećera i masnih kiselina su biorazgradive površinski aktivne materije čija je primena značajna u proizvodnji hrane, kozmetičkih preparata i lekova. To su potencijalne supstance koje se mogu iskoristiti umesto nekih drugih hemijski sintetizovanih površinski aktivnih materija koji se danas smatraju da su zagađivači životne sredine. Enzimska sinteza palmitata fruktoze katalizovane lipazom Candida antarctica B analizirana je u šaržnom reaktoru pod atmosferskim pritiskom u prisustvu različitih organskih rastvarača pri čemu je proučavan uticaj organskog rastvarača i temperature na brzinu esterifikacije, s obzirom da natkritični ugljen dioksid (SC CO2) poseduje značajne prednosti u odnosu na klasične organske rastvarače jer se u složenim procesima može uvećati brzina hemijske reakcije kao i brzina prenosa mase u prisustvu SC CO2. Nadalje ovaj ugušćeni fluid je netoksičan, nezapaljiv i može se nabaviti po niskoj ceni te je izabran kao medijum za reakciju esterifikacije fruktoze i palmitinske kiseline i dobijanja palmitata fruktoze. Uticaj temperature na brzinu esterifikacije u prisustvu imobilisane lipaze proučavan je na 10 MPa i dobijeni rezultati su upoređivani sa rezultatima esterifikacije pod atmosferskim pritiskom na istim temperaturama. Najveća konverzija od 67% je ostvarena nakon 24 h kada je reakcija esterifikacije realizovaná na 80°C u prisustvu SC CO2. Ispitivan je uticaj raspodele veličine čestica i morfologije netretirane i tretirane lipaze sa 2-metil 2-butanolom i SC CO2 na brzinu procesa esterifikacije fruktoze i palmitinske kiseline.